In situ electronic structural study of VO2 thin film across the metal–insulator transition - 伊明江·买买提 阿布都艾则孜·阿布来提 吴蕊 王嘉鸥 钱海杰 奎热西·依布拉欣 (中国物理B：英文版, 2013)
The in situ valence band photoemission spectrum （PES） and X-ray absorption spectrum （XAS） at V LⅡ-LⅢ edges of the VO2 thin film, which is prepared by pulsed laser deposition, are measured across the metal–insulator transition （MIT） temperature （TMIT=67 ℃）. The spectra show evidence for changes in the electronic structure depending on temperature. Across the TMIT, pure V 3d characteristic d‖ and O 2p-V 3d hybridization characteristic πpd, σpd bands vary in binding energy position and density of state distributions. The XAS reveals a temperature-dependent reversible energy shift at the V LⅢ-edge. The PES and XAS results imply a synergetic energy position shift of occupied valence bands and unoccupied conduction band states across the phase transition. A joint inspection of the PES and XAS results shows that the MIT is not a one-step process, instead it is a process in which a semiconductor phase appears as an intermediate state. The final metallic phase from insulating state is reached through insulator–semiconductor, semiconductor–metal processes, and vice versa. The conventional MIT at around the TMIT=67 ℃ is actually a semiconductor–insulator transformation point.